Frontalis Brow Suspension for Congenital Ptosis using Silicon Dacrocystorhinostomy Tube with Three Months Follow up - Kashif Ali; Sameer Shahid Ameen; M. Asim Mehmood; Khalid (Journal of Bahria University Medical and Dental College)
Primary congenital ptosis usually presents at the time of birth and is due to poor development of levator muscles.The frontalis brow suspension technique is being used for patients with severe congenital ptosis and a levator function of 4 mm or less. Oculoplastic surgeons have been using different artificial materials not only to avoid an accessory wound and bleeding, but also to shorten the surgical time. Several artificial materials (e.g., nylon suture, silicone rods) have been used for congenital ptosis surgery. In this case report we have used silicon dacrocystorhinostomy (DCR) tube for frontalis brow suspension. This synthetic tube is readily available as well as cost effective with promising results post operatively for congenital ptosis correction with Frontalis Brow Suspension Technique.